Influence of Periapical Lesion on Healing in Sinus after Endodontics - Migas, Klaudia; Marchlewska, Joanna (European Journal of General Dentistry, 2022)
Objective The goal of primary and secondary endodontic treatment is to eliminate the cause of inflammation inside the tooth and in the surrounding tissues. When the inflammation from the root canal system of the tooth spreads beyond the apex of the root, periapical changes in the bone tissue and, in the case of upper premolars and molars, inflammatory changes in the Schneider membrane may occur.Materials and Methods In a retrospective documentation analysis of root canal treatments, three-dimensional (3D) computed tomography images before and after endodontic treatment were assessed to measure the thickness of the Schneider membrane. Forty-five endodontically treated patients aged 21 to 62 years were enrolled in the study. Inflammation of the maxillary sinus was considered when the Schneider membrane was thicker than 2 mm. Statistical analyses were performed with Statistica 12 by StatSoft and StatXact by Cytel using the Shapiro–Wilk test, Student's t-test, and the Mann–Whitney test.Results Out of 12 comparisons between variables, only 3 comparisons were significant. There was a relationship between the treatment effect (reduction in maxillary sinus inflammation 3 months after treatment) and the maximum height of the Schneider membrane (p = 0.004). There was a relationship between the presence of a periapical lesion and the minimum height of the Schneider diaphragm (p = 0.02), and there was a relationship between the presence of a periapical lesion and the maximum height of the Schneider diaphragm (p = 0.04).Conclusion Primary and secondary root canal treatments of maxillary premolars and molars reduce the inflammation of the maxillary sinus 3 months after treatment.
Keywords: root canal treatment; Schneider's membrane; maxillary sinus inflammation; periapical lesion